Long-term Safety and Efficacy of Avalglucosidase Alfa in Patients With Late-Onset Pompe Disease. (2nd August 2022) - Dimachkie, Mazen M.; Barohn, Richard J.; Byrne, Barry; Goker-Alpan, Ozlem; Kishnani, Priya S.; Ladha, Shafeeq; Laforêt, Pascal; Mengel, Karl Eugen; Peña, Loren D.M.; Sacconi, Sabrina; Straub, Volker; Trivedi, Jaya; et al.
Abstract : Background and Objectives: Pompe disease is a rare, progressive neuromuscular disorder caused by deficiency of lysosomal acid α-glucosidase (GAA) and subsequent glycogen accumulation. Avalglucosidase alfa, a recombinant human GAA enzyme replacement therapy designed for increased cellular uptake and glycogen clearance, has been studied for long-term efficacy and safety in patients with late-onset Pompe disease (LOPD). Here, we report up to 6.5 years' experience with avalglucosidase alfa during the NEO1 and NEO-EXT studies. Methods: NEO1 participants with LOPD, either treatment naive (Naive Group) or receiving alglucosidase alfa for ≥9 months (Switch Group), received avalglucosidase alfa (5, 10, or 20 mg/kg every other week [qow]) for 6 months before entering NEO-EXT and continued their NEO1 dose until all proceeded with 20 mg/kg qow. Safety and efficacy, a prespecified exploratory secondary outcome, were assessed; slopes of change for efficacy outcomes were calculated from a repeated mixed-measures model. Results: Twenty-four participants enrolled in NEO1 (Naive Group, n = 10; Switch Group, n = 14); 21 completed and 19 entered NEO-EXT; in February 2020, 17 participants remained in NEO-EXT, with data up to 6.5 years. Avalglucosidase alfa was generally well tolerated during NEO-EXT, with a safety profile consistent with that in NEO1. No deaths or treatment-related life-threatening serious adverse events occurred. Eighteen participants developed antidrug antibodies without apparent effect on clinical outcomes. No participants who were tested developed immunoglobulin E antibodies. Upright forced vital capacity %predicted remained stable in most participants, with slope estimates (95% CIs) of −0.473 per year (−1.188 to 0.242) and −0.648 per year (−1.061 to −0.236) in the Naive and Switch Groups, respectively. Six-minute walk test (6MWT) %predicted was also stable for most participants, with slope estimates of −0.701 per year (−1.571 to 0.169) and −0.846 per year (−1.567 to −0.125) for the Naive and Switch Groups, respectively. Improvements in 6MWT distance were observed in most participants aged <45 years at NEO1 enrollment in both the Naive and Switch Groups. Discussion: Avalglucosidase alfa was generally well tolerated for up to 6.5 years in adult participants with LOPD either naive to alglucosidase alfa or who had previously received alglucosidase alfa for ≥9 months. Classification of Evidence: This study provides Class IV evidence of long-term tolerability and sustained efficacy of avalglucosidase alfa in patients with LOPD after up to 6.5 years. Trial Registration Information: NCT01898364 (NEO1 first posted: July 12, 2013; clinicaltrials.gov/ct2/show/NCT01898364 ); NCT02032524 (NEO-EXT first posted: January 10, 2014; clinicaltrials.gov/ct2/show/NCT02032524 ). First participant enrollment: NEO1—August 19, 2013; NEO-EXT—February 27, 2014.